2002
DOI: 10.1006/exer.2002.2013
|View full text |Cite
|
Sign up to set email alerts
|

Deletional Analysis of the Rod Photoreceptor Cell Peripherin/RDS Carboxy-Terminal Region

Abstract: The C-terminal region of peripherin/rds contains three predicted α-helical domains. One of these domains, corresponding to amino acids 311-322, form an amphiphilic α-helix previously shown to promote membrane fusion. The present studies were conducted to determine how the additional α-helical regions of the peripherin/rds C-terminus affect complex formation with rom-1, glycosylation, intracellular localization and membrane fusion properties. Bovine peripherin/rds and rom-1 were epitope tagged with an amino-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…This region of P/rds has been found to promote membrane fusion activity as well as membrane targeting (13,14,35). Past experiments have shown that the deletion of the C-terminal tail of P/rds abolishes the fusogenic activity but does not have any negative effects on protein dimerization or complex assembly with Rom-1 (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This region of P/rds has been found to promote membrane fusion activity as well as membrane targeting (13,14,35). Past experiments have shown that the deletion of the C-terminal tail of P/rds abolishes the fusogenic activity but does not have any negative effects on protein dimerization or complex assembly with Rom-1 (14).…”
Section: Discussionmentioning
confidence: 99%
“…This region of P/rds has been found to promote membrane fusion activity as well as membrane targeting (13,14,35). Past experiments have shown that the deletion of the C-terminal tail of P/rds abolishes the fusogenic activity but does not have any negative effects on protein dimerization or complex assembly with Rom-1 (14). In addition to the fusogenic activity and membrane targeting, the C terminus of P/rds may be involved in anchoring the protein or connecting the disk rim to the plasma membrane through associations with auxiliary proteins, cytoskeleton proteins, or plasma-membrane proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROM-1 forms a hetero-tetrameric complex with P/rds both in vivo and in heterologous cell expression systems (Goldberg, Moritz et al 1995;Muller-Weeks, Boesze-Battaglia et al 2002). Even though the domain involved in tetramerization has been mapped to Cys 165 -Asn 182 of P/rds the precise role of ROM-1 in P/rds dependent function has remained elusive.…”
Section: Resultsmentioning
confidence: 99%
“…Procedures for the isolation and cloning of bovine FLAG-tagged peripherin/rds ( FLAG-P/ rds) and hemaglutininin-tagged ROM-1, ( HA-ROM-1) have previously been described (Muller-Weeks, Boesze-Battaglia et al 2002). Primer design was based on sequences reported by (Connell and Molday 1990) and (Moritz and Molday 1996).…”
Section: Plasmid Constructsmentioning
confidence: 99%